Il mondo sfolgorante di Lauretta Vinciarelli - De Rosa, Agostino (Firenze Architettura, 2019)
The graphic work by Lauretta Vinciarelli (1943-2011) invites the observer to enter a universe of suspended visions, of archetypal places dominated by reflections and atmospheric fluidity. An architect and university professor in the United States, Lauretta Vinciarelli painted and made drawings moved by the wish to figuratively tap into the sunny Roman atmosphere where she came from, but also into the sweltering dryness of the Texas deserts, where she lived with partner and fellow-artist Donald Judd.